Antique Dealing and Creative Reuse in Cairo and Damascus 1850-1890 : Intercultural Engagements with Architecture and Craft in the Age of Travel and Reform - Volait, Mercedes, (Leiden Studies in Islam and Society ;, 2021)
"The commodification of Islamic antiques intensified in the late Ottoman Empire, an age of domestic reform and increased European interference following the Tanzimat (reorganisation) of 1839. Mercedes Volait examines the social life of typical objects moving from Cairo and Damascus to Paris, London, and beyond, uncovers the range of agencies and subjectivities involved in the trade of architectural salvage and historic handicraft, and traces impacts on private interiors, through creative reuse and Revival design, in Egypt, Europe and America. By devoting attention to both local and global engagements with Middle Eastern tangible heritage, the present volume invites to look anew at Orientalism in art and interior design, the canon of Islamic architecture and the translocation of historic works of art"--